2018
DOI: 10.1177/1359105318763505
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring patterns of post-traumatic stress disorder and depression among flood victims: A latent profile analysis

Abstract: This study examined the co-occurring patterns of post-traumatic stress disorder and depression. A sample of 187 victims completed self-report questionnaires after a major flood disaster. Results indicated four classes: low symptoms group (49.7%), mild comorbid symptoms group (24.1%), serious comorbid symptoms group (3.2%), and medium comorbid symptoms group (23.0%). Male victims were less likely and older victims were more likely to belong to the medium comorbid symptoms group; victims with more serious trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 64 publications
(91 reference statements)
5
8
2
Order By: Relevance
“…The possible explanation for this is that with increasing age, individuals accumulate more experience facing negative events and have more psychological energy to deal with catastrophic events (Amir & Ramati, 2002 ). Sex and cause of death had no predictive effects in this study, which was inconsistent with the results of some prior studies (Cao et al, 2018 ; Zhen et al, 2018 ). The main reason for these results may lie in the intricacies of Chinese culture.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The possible explanation for this is that with increasing age, individuals accumulate more experience facing negative events and have more psychological energy to deal with catastrophic events (Amir & Ramati, 2002 ). Sex and cause of death had no predictive effects in this study, which was inconsistent with the results of some prior studies (Cao et al, 2018 ; Zhen et al, 2018 ). The main reason for these results may lie in the intricacies of Chinese culture.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, the high symptom group proportion (27.8%) was higher than that reported in previous studies (from 5.4% to 9.0%; Cao et al, 2015 ; Zhen et al, 2019 ). The moderate symptom group proportion (32.8%) was close to that identified in Armour et al ( 2015 ); however, it was higher than some other previous studies (Zhen, Quan, & Zhou, 2018 ; Zhen et al, 2019 ). The low symptom group proportion (39.4%) was smaller than those identified in previous studies (Cao et al, 2015 ; Zhen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Guo et al showed a similar association between age and PTSD among 1369 earthquake survivors in China. [19] Nevertheless, other reports either failed to show an association between age and PTSD [20] or showed a positive association, [21][22][23] which is opposite to the reported results in this study. The latter studies were all conducted post-natural (earthquake or flood) disasters.…”
Section: Discussioncontrasting
confidence: 99%
“…There is a consensus in the literature that females have higher odds of having PTSD than males, and the prevalence of PSTD among females is higher than that in males. [ 19 , 22 , 23 , 26 , 27 ] Along these lines, multiple reports in the literature showed a high association between depression and PTSD in adults and adolescents. [ 26 , 28 , 29 ] For instance, in a cohort conducted by Jordan et al, including 36,897 participants, the prevalence of PTSD and depression in survivors of the 9/11 World Trade Center terrorist attacks was 14.3% and 15.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%